DENTAL CONDITION OF PERIODONTAL TISSUES IN PATIENTS WITH PSYCHIATRIC PATHOLOGY - Gafforov S. A; Astanov O. M (Scholar Express Journals, 2023)
According to the results of the study, an increase in the incidence of cerebral palsy (CP) was noted in Uzbekistan; taking these results into account, the authors studied the morphometric parameters and deformations of the teeth and dentofacial system in children and adolescents with cerebral palsy. It has been established that the study population is at a very high risk of developing deformations of the teeth and the dentofacial system, as well as a connection with morphometric growths of the oblique elements of the dentofacial system
Keywords: anomalies; deformations; teeth